China-USA economic relations: bilateral ties and multilateral economic projects - S. M. Troush (Сравнительная политика, 2017)
The article is devoted to the study of problematic issues of the change of US-China trade is going up notwithstanding the slowdown of Chinese economy. Those US fi rms who placed production in China became more involved into Chinese internal market. Chinese investments into US prevail over the US investments in China. The decisions of the Chinese leadership to set up the new market priorities in the economic development are implemented with obvious diffi culties, but being implemented, could stimulate US-China ties.